Increasing the abundance of microorganisms in a regosol soil using biopelet fertilizer composed from biochar, chicken manure, and shrimp waste to increase soil fertility - Sugeng Winarso; Wachju Subchan; Tri Candra Setiawati; Sukron Romadhona Sukron Romadhona (Brawijaya University, 2021)
Results of previous research have proven that soil organic matter (humic and biochar compounds) can increase and maintain soil fertility and protect environmental resilience. The purpose of this study was to increase the abundance of microorganisms in young soil (regosol) with biopelet fertilizer composed of a combination of biochar, chicken manure, and shrimp waste to improve soil fertility. The experimental design used was a randomized block design with two factors, namely the composition and dosage of biopelets. The compositions of biopelet were 70% biochar, 15% chicken manure and 15% fish waste (B1); 50% biochar, 25% chicken manure and 25 % fish waste (B2): and 20% biochar, 40% chicken manure and 40% fish waste (B3). The dosage used was four levels (0, 2.5, 5, and 10 t/ha).The results showed that the application of biopelet fertilizer to the regosol soil reduced soil pH from slightly alkaline to near neutral, and the addition of up to 10 t biopelet/ha increased soil organic C content from 1.17% to 1.72%, as well as increasing the availability of N, P, and K nutrients. Improvement in pH, organic-C, and soil macronutrients was followed by an increase in the abundance of soil microorganisms, especially bacteria.